Photochemical Synthesis of the Bioconjugate Folic Acid-Gold Nanoparticles - John Castillo; Linda Bertel; Edgar Páez-Mozo; Fernando Martínez (Nanomaterials and Nanotechnology, 2013)
In this paper we present a rapid and simple onepot method to obtain gold nanoparticles functionalized with folic acid using a photochemistry method. The bioconjugate folic acid-gold nanoparticle was generated in one step using a photo-reduction method, mixing hydrogen tetrachloroaurate with folic acid in different ratios and varying the illumination time of a mercury lamp (λ= 255 nm). Scanning electron microscopy showed a particle size of around 40-50nm and dynamic light scattering exhibited that the zeta potential varies from -41 to -50mV with different illumination times. Storage in the dark at 4°C prolongs the stability of folic acid-gold nanoparticle suspensions to up to 26 days. Ultraviolet visible and Fourier transform infrared spectroscopy showed a surface plasmon band of around 534nm and fluorescence spectroscopy exhibited a quenching effect on gold nanoparticles in the fluorescence emission of folic acid and thus confirmed the conjugation of folic acid to the surface of gold nanoparticles. In this study we demonstrate the use of a photochemistry method to obtain folic acid-gold nanoparticles in a simple and rapid way without the use of surfactants and long reaction times. The photochemical synthesis of FA-AuNPs opens new perspectives for creating novel functional nanomaterials for biomedical applications.